Note : Probably, you made a mistake in writing the assignment. I will correct the task so that it can be solved.
Solve ordinary differential equation :
"\\frac{d^2y}{dx^2}-2x\\cdot\\frac{dy}{dx} + (x^2+2)y= \\sqrt{e}(x^2+2)"
From the theory we know that for solving the equation
"y''+f(x)\\cdot y'+g(x)\\cdot y=F(x)"
convenient to introduce a new variable
"y(x)=k(x)\\cdot exp\\left(-\\frac{1}{2}\\cdot\\int f(x)dx\\right)"
In our case,
"\\frac{d^2y}{dx^2}\\underbrace{-2x}_{f(x)}\\cdot\\frac{dy}{dx} +\\underbrace{(x^2+2)}_{g(x)}y= \\underbrace{\\sqrt{e}(x^2+2)}_{F(x)}"
Then,
"f(x)=-2x\\to-\\frac{1}{2}\\cdot\\int f(x)dx=-\\frac{1}{2}\\cdot\\int (-2x)dx=\\frac{x^2}{2}\\\\[0.3cm]\ny(x)=k(x)\\cdot e^{x^2\/2}\\to \\frac{dy}{dx}=k'\\cdot e^{x^2\/2}+xk\\cdot e^{x^2\/2}\\\\[0.3cm]\n\\boxed{\\frac{dy}{dx}=e^{x^2\/2}\\cdot\\left(k'+xk\\right)}\\\\[0.3cm]\n\\frac{d^2y}{dx^2}=k''\\cdot e^{x^2\/2}+xk'\\cdot e^{x^2\/2}+k\\cdot e^{x^2\/2}+xk'\\cdot e^{x^2\/2}+x^2k\\cdot e^{x^2\/2}\\\\[0.3cm]\n\\boxed{\\frac{d^2y}{dx^2}=e^{x^2\/2}\\cdot\\left(k'' +2xk'+k+x^2k\\right)}"
We substitute the found derivatives into the initial equation
"\\frac{d^2y}{dx^2}-2x\\cdot\\frac{dy}{dx}+(x^2+2)\\cdot y=\\sqrt{e}\\cdot(x^2+2)\\\\[0.3cm]\ne^{x^2\/2}\\cdot\\left(k'' +2xk'+k+x^2k\\right)-2x\\cdot e^{x^2\/2}\\cdot\\left(k'+xk\\right)+\\\\[0.3cm]\n\\left.+(x^2+2)\\cdot e^{x^2\/2}\\cdot k=\\sqrt{e}\\cdot(x^2+2)\\right|\\div\\left(e^{-x^2\/2}\\right)\\\\[0.3cm]\nk'' +2xk'+k+x^2k-2xk'-2x^2k+x^2k+2k=e^{-x^2\/2}\\cdot\\sqrt{e}\\cdot(x^2+2)\\\\[0.3cm]\nk''+3k=e^{-x^2\/2}\\cdot\\sqrt{e}\\cdot(x^2+2)"
This is a second order inhomogeneous equation. The solutions will have the form :
"k(x)=k_{hom}(x)+k_{part}(x),\\,\\,\\,\\text{where}\\\\[0.3cm]\nk_{hom}(x) : k''+3k=0\\to k(x)=e^{\\lambda x}\\to\\\\[0.3cm]\nk'(x)=\\lambda\\cdot e^{\\lambda x}\\,\\,\\,\\text{and}\\,\\,\\, k''(x)=\\lambda^2\\cdot e^{\\lambda x}\\\\[0.3cm]\ne^{\\lambda x}\\cdot(\\lambda^2+3)=0\\to\n\\left[\\begin{array}{l}\n\\lambda_1=i\\sqrt{3}\\\\[0.3cm]\n\\lambda_2=-i\\sqrt{3}\n\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\nk_{hom}(x)=A_1\\cdot e^{i\\sqrt{3}x}+A_2\\cdot e^{-i\\sqrt{3}x}\\equiv C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)\\\\[0.3cm]\n\\boxed{k_{hom}(x)= C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)}"
We look for a particular solution in the form
"k_{part}(x)=e^{-x^2\/2}\\cdot\\left(Ax^2+Bx+C\\right)\\\\[0.3cm]\nk''=\\left(e^{-x^2\/2}\\right)''\\cdot\\left(Ax^2+Bx+C\\right)+2\\left(e^{-x^2\/2}\\right)'\\left(Ax^2+Bx+C\\right)'\\\\[0.3cm]\n+e^{-x^2\/2}\\left(Ax^2+Bx+C\\right)''\n=e^{-x^2\/2}(x^2-1)\\left(Ax^2+Bx+C\\right)+\\\\[0.3cm]+e^{-x^2\/2}(-2x)\\left(2Ax+B\\right)\n+e^{-x^2\/2}(2A)\\\\[0.3cm]\nk''+3k=e^{-x^2\/2}((x^2-1)\\left(Ax^2+Bx+C\\right)-4Ax^2-2Bx+2A)\\to\\\\[0.3cm]\ne^{-x^2\/2}((x^2-1)\\left(Ax^2+Bx+C\\right)-4Ax^2-2Bx+2A)+\\\\[0.3cm]\n\\left.+3\\cdot e^{-x^2\/2}(Ax^2+Bx+C)=e^{(1-x^2)\/2}(x^2+2)\\right|\\div\\left(e^{-x^2\/2}\\right)\\\\[0.3cm]\nAx^4+Bx^3+Cx^2-Ax^2-Bx-C-4Ax^2-2Bx+2A+\\\\[0.3cm]\n+3Ax^2+3Bx+3C=\\sqrt{e}(x^2+2)\\\\[0.3cm]\nAx^4+Bx^3+(C-2A-\\sqrt{e})x^2+(2A+2C-2\\sqrt{e})=0\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\nx^4 : A=0\\\\[0.3cm]\nx^3 : B=0\\\\[0.3cm]\nx^2 : C-2A-\\sqrt{e}=0\\to C=\\sqrt{e}\\\\[0.3cm]\nx^0 : 2A+2C-2\\sqrt{e}=0\n\\end{array}\\right."
Conclusion,
"\\boxed{k_{part}(x)=e^{-x^2\/2}\\cdot\\sqrt{e}}"
Then,
"k(x)=k_{hom}(x)+k_{part}(x)\\to\\\\[0.3cm]\n\\boxed{k(x)=C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)+e^{-x^2\/2}\\cdot\\sqrt{e}}"
Finally, general solution is
"y(x)=e^{x^2\/2}\\cdot k(x)=\\\\[0.3cm]\n=\\left(C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)+e^{-x^2\/2}\\cdot\\sqrt{e}\\right)\\cdot e^{x^2\/2}\\to\\\\[0.3cm]\n\\boxed{y(x)=\\left(C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)\\right)\\cdot e^{x^2\/2}+\\sqrt{e}}"
ANSWER
"y(x)=\\left(C_1\\cos\\left(\\sqrt{3}x\\right)+C_2\\sin\\left(\\sqrt{3}x\\right)\\right)\\cdot e^{x^2\/2}+\\sqrt{e}"
Comments
Leave a comment